Influence of kaempferol against garri meal tainted with vacuum gas oil induced nephro- and neurotoxicity - Joel Okpoghono; Busade Adebayo Agbetuyi; Toritseju Eyide; Innocent Onyesom (Food Chemistry Advances)
The present study investigated the defensive effect of kaempferol in the tissues of Wistar rats fed with vacuum gas oil polluted garri diet. The rats (30) were grouped into six (n = 5): Group 1: Control: Fried garri normal diet (FGND). Group 2 and 3 were given FGND and treated with 50 and 100 mg/kg b. wt of kaempferol. Group 4: Fried garri diet with vacuum gas oil (FGD-VGO) only. Group 5 and 6 were given FGD-VGO then treated with 50 and 100 mg/kg b. wt. of kaempferol. The rats were euthanized using carbon dioxide after experimental period of 28 days. The tissues (kidney and brain) were excised for biochemical assays. The results indicated a significant decrease in antioxidant markers (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione-s-transferase, GST), Na+/K+-ATPase, percentage of fragmented deoxyribonucleic acid (DNA) and increase malondialdehyde (MDA) in the tissues of rats in group 4 compared to the other groups. However, treatment with kaempferol significantly decreased MDA level and increased antioxidant markers in the tissues of rats fed FGD-VGO. In conclusion, the data obtained may point out to kaempferol playing a crucial role as an antioxidant against garri meal tainted with vacuum gas oil in Wistar rats.